Recensão / Review: JASPERSE, Jitske – Medieval Women, Material Culture, and Power. Matilda Plantagenet and her Sisters. Leeds: ARC Humanities Press, 2020 (134 pp.) - Maciel Regalado, Cynthia (Medievalista, 2023)
Referências bibliográficas BENNETT, Judith; KARRAS, Ruth – The Oxford Handbook of Women and Gender in Medieval Europe. Oxford: Oxford University Press, 2013. BISSON, Thomas N. – The Crisis of the Twelfth Century. Power, Lordship, and the Origins of European Government. New Jersey: Princeton University Press, 2009. CORRAL DÍAZ, Esther – “Modelos de reinas en relación con la lírica gallego-portuguesa: el mecenazgo de Leonor Plantagenet y Berenguela de Barcelona”. In GONZÁLEZ DORESTE, Dulce María; PLAZA PICÓN, Francisca del Mar – Estereotipos femeninos desde la Antigüedad clásica hasta el siglo XVI. Berlin – Boston: De Gruyter, 2022, pp. 59-74. ERLER, Mary; Kowaleski, Maryanne – Gendering the Master Narrative: Women and Power in the Middle Ages. Ithaca: Cornell University Press, 2003.